http://www.revistanavigator.com.br/navig12/dossie/N12_dossie6.html - Lúcia Maria Bastos Pereira das Neves; Lucia Maria Paschoal Guimarães; Tânia Bessone da Cruz Ferreira (Navigator)
Chineses developed peculiar relations with Brazil, even so they did not represent a great immigratory chain. In the colonial times, it had a continuous interchange between China and Brazil by means of traders, religious, magistrates and adventurers, who in such a way travelled among the Portuguese territories. After the transference of the Portuguese Court to Rio de Janeiro, prince regent d. João ordered to bring three hundred Chinese from Macau to come to Rio to plant tea in the just established Botanical Garden. At the end 1870, there were some efforts to encourage the Chinese immigration to Brazil to substitute the african slaves in the great plantations. In spite of the diplomatics efforts, the negotiations did not go on, because Brazilian authorities preferred to engage European immigrants.